Games as Tools to Address Conservation Conflicts. (June 2018) - Redpath, Steve M.; Keane, Aidan; Andrén, Henrik; Baynham-Herd, Zachary; Bunnefeld, Nils; Duthie, A. Bradley; Frank, Jens; Garcia, Claude A.; Månsson, Johan; Nilsson, Lovisa; Pollard, Chris R.J.; Rakotonarivo, O. Sarobidy; et al.
Abstract : Conservation conflicts represent complex multilayered problems that are challenging to study. We explore the utility of theoretical, experimental, and constructivist approaches to games to help to understand and manage these challenges. We show how these approaches can help to develop theory, understand patterns in conflict, and highlight potentially effective management solutions. The choice of approach should be guided by the research question and by whether the focus is on testing hypotheses, predicting behaviour, or engaging stakeholders. Games provide an exciting opportunity to help to unravel the complexity in conflicts, while researchers need an awareness of the limitations and ethical constraints involved. Given the opportunities, this field will benefit from greater investment and development.